Validity of autorefractor based screening method for irregular astigmatism compared to the corneal topography- a cross sectional study - Galindo-Ferreiro, Alicia; De Miguel-Gutierrez, Julita; González-Sagrado, Manuel; Galvez-Ruiz, Alberto; Khandekar, Rajiv; Schellini, Silvana [UNESP]; Galindo-Alonso, Julio (Press of International Journal of Ophthalmology (IJO Press), 2017)
● AIM: To present a method of screening for irregular astigmatism with an autorefractor and its determinants compared to corneal topography. ● METHODS: This cross-sectional validity study was conducted in 2013 at an eye hospital in Spain. A tabletop autorefractor (test 1) was used to measure the refractive status of the anterior surface of the cornea at two corneal meridians of each eye. Then corneal topography (test 2) and Bogan’s classification was used to group eyes into those with regular or no astigmatism (GRI) and irregular astigmatism (GRII). Test 1 provided a single absolute value for the greatest cylinder difference (Vr). The receiver operating characteristic (ROC) were plotted for the Vr values measured by test 1 for GRI and GRII eyes. On the basis a Vr value of 1.25 D as cut off, sensitivity, specificity were also calculated. ● RESULTS: The study sample was comprised of 260 eyes (135 patients). The prevalence of irregular astigmatism was 42% [95% confidence interval (CI): 36, 48]. Based on test 2, there were 151 eyes in GRI and 109 eyes in GRII. The median Vr was 0.75 D (25% quartile, 0.5 D) for GRI and 1.75 D (25% quartile, 1.25 D) for GRII. The area under curve was 0.171 for GRI and 0.83 for GRII. The sensitivity of test I was 78.1% and the specificity was 76.1%. ● CONCLUSION: A conventional autorefractor can be effective as a first level screening method to detect irregular corneal astigmatism in places where corneal topography facilities are not available.
Keywords: Autorefractor; Cornea; Corneal topography; Irregular astigmatism; Screening; Validity